Gender violence in media: A study of Kaduna state media corporation (ksmc) - Ofordi, Joy Amarachi; Salisu, Abdullahi (Journal of Language, Literature, Social and Cultural Studies, 2024)
Gender violence is a global pandemic that has permeated every sector of human life including the media. It is a major public health and human rights problem involving all ages and sexes however, women in media, have taken quite the hit in the form of threats or abuse in connection with their work, as victims of intimidation, sexual harassment, deprivations of liberty or certain rights. As a result, this research investigated gender violence in Kaduna State Media Corporation (KSMC). Amongst others, this study purposes to identify the various forms of gender violence and the causes of gender violence in Kaduna State Media Corporation. Anchored on the feminist theory, the research combines qualitative analysis of relevant literature with primary data collected through in-depth interviews in which 10 participants from both genders, were purposively selected media professionals in Kaduna State Media Corporation. The findings show that gender violence exists in KSMC against women, in very subtle forms of abuse of power, assault, psychological abuse, and discrimination however, they have put in preventive such as sensitization programs and workshops to combat gender violence. The study, therefore recommends that media organizations should try and employ more women in their organizations and also, anyone found assaulting his female colleague should be severely punished, as the workplace ought to be conducive for everyone.